2009
DOI: 10.1523/jneurosci.4943-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Feedback-Related Potentials in Nonhuman Primates: Modulation during Learning and under Haloperidol

Abstract: Feedback monitoring and adaptation of performance involve a medial reward system including medial frontal cortical areas, the medial striatum, and the dopaminergic system. A considerable amount of data has been obtained on frontal surface feedback-related potentials (FRPs) in humans and on the correlate of outcome monitoring with single unit activity in monkeys. However, work is needed to bridge knowledge obtained in the two species. The present work describes FRPs in monkeys, using chronic recordings, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…Once monkeys had found the rewarded location, they could repeat that rewarded choice three times (repetition phase, REP), before a signal to change (STC) informed them that the rewarded location had been re-randomized. Previous research has shown that the PST induces high or low cognitive control on different trials [8,12,18,23]. Low control is sufficient on any repetition trial after correct feedback, as the monkey simply has to repeat the previous choice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once monkeys had found the rewarded location, they could repeat that rewarded choice three times (repetition phase, REP), before a signal to change (STC) informed them that the rewarded location had been re-randomized. Previous research has shown that the PST induces high or low cognitive control on different trials [8,12,18,23]. Low control is sufficient on any repetition trial after correct feedback, as the monkey simply has to repeat the previous choice.…”
Section: Resultsmentioning
confidence: 99%
“…High control is required when the outcome of the previous trial necessitates a behavioural adaptation—notably, in three cases, after an incorrect feedback, after an STC directing a new SEA phase, and after the monkey makes a break in fixation or touch. This task is a well-established test of cognitive control with well-established neural correlates, notably delay activity in PFC comparable to working memory tasks [18] and feedback responses sensitive to dopamine [8]. As such, it allows us to probe control in terms of both performance monitoring and control implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, we adapted a problem-solving task developed for electrophysiological recording in monkeys (Quilodran et al, 2008;Rothe et al, 2011;Vezoli and Procyk, 2009). Subjects had to discover which one of the four presented stimuli was associated with correct feedback (i.e.…”
Section: Introductionmentioning
confidence: 99%